Running blind: the sensory practices of visually impaired runners - Powis, B.; Macbeth, J. L. (Qualitative Research in Sport, Exercise and Health, 2023)
In this article, we consider what it means to be running blind. As an idiom, this phrase refers to doing something through guesswork, without a plan or pre-existing knowledge; instead, our notion of running blind offers an alternative perspective. Drawing upon a novel theoretical approach, which is multidisciplinary and engages with the work of visually impaired (VI) and non-VI scholars, we establish the rich, creative and diverse sensory practices of VI runners. The data in this article is drawn from a qualitative study involving eight blind and partially sighted participants, who each took part in two semi-structured interviews. Using abductive analysis, our discussion is organised around the route: 1) Knowing the route; 2) Navigating the route; and 3) Pleasures of the route. While VI runners` sensory practices are unique, there are significant commonalities in our participants` experiences of running blind, including the mapping process, agency and freedom en route, multisensorial modes of navigation and more-than-visual running pleasures. This article demonstrates the importance of exploring non-ocularnormative conceptions of sport and physical activity, which is of value for VI runners, guide runners and key stakeholders alike.